(untitled) (University of Thi-Qar Journal for Engineering Sciences, 2022)
The smart stretcher is a device used to transport individuals who need medical attention, the stretchers are typically utilized by emergency medical services (EMS). The suggested prototype of smart stretcher model consist of A two-parts: the upper part (portable stretcher consist of central bed, middle part and handle part), and the lower part consist of the passive and active suspension systems. The portable stretcher is suggested to reduce the disturbance to patient, where the control system is consist of the Arduino Uno, two stepper motors (for controlling the pitch and the roll motions), the MPU6050 for sensing the roll and pitch angles of handling part and two of the SC60C sensors are placed in the central bed for measure it’s the roll and the pitch angles. In this study, the Simulink/MATLAB was used to investigated and controlling by using the PID controller with the active suspension to reduce the vibrations which transfer to upper part. Form the suggested model of smart stretcher can conclude the active suspension show the effective suspension and can be use in transporting of patients.